The Effect of Service Quality and Customers’ Relationship Management on Customers’ Loyalty at Bank BSI KC Bengkulu S. Parman 2 - Mita Handayani; Merta Kusuma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
Bank Syariah Indonesia provides more complete services, wider reach, and has a better capital capacity.It is spported by synergies with parent companies (Mandiri, BNI, BRI) and the government's commitment through the Ministry of SOEs. Bank Syariah Indonesia is encouraged to be able to compete at the global level. This study aimed to determine the effect service quality and customers’ relationship management on customers’ loyalty at Bank BSI KC Bengkulu S. Parman 2. This data of the study was obtained through observation and distributing questionnaire. It was distributed to 110 respondents, namely customers who saved at Bank BSI KC Bengkulu S. Parman 2. The data was analyzed by using quantitative data analysis. The quantitative analysis includes instrument testing, classical assumption test, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression test by using the SPSS program, namely Y = Y = 4.388 + 0.158 (X1) + 0.357 (X2). The result of the coefficient of determination (R2) the value of R Square is 0.718 or 71.8%, where the coefficient of determination means that together the service quality and customers’ relationship management variables contribute to give effect on customers’ loyalty at Bank BSI KC Bengkulu S. Parman 2 , while the remaining 0.282 or 28.2% is influenced by other variables outside the study. The hypothesis testing by using t test and F test shows that service quality (X1) and customers’ relationship management (X2) variables have a significant effect on customers’ loyalty (Y), where the significance level is <0.05. This means that Ho is rejected and Ha is accepted.